From the pandemic to spiraling inflation: Moral superiority over the Argentine state in times of crisis - Ariel Wilkis (economic sociology. perspectives and conversations, 2023)
Between 2020 and 2022, two major events shook society, the economy, and the daily lives of people across the world.1 The first of these events, the Covid-19 pandemic, set off a new cycle of inflation after several decades in which prices had been at a virtual standstill for most countries worldwide. In order to understand these two processes, their interactions, and their conditioning factors, this article focuses on the emerging sense among Argentines of their moral superiority to the state since the outbreak of the pandemic.
Keywords: 300